Bone densitometry status and its associated factors in peri and post menopausal females: A cross sectional study from a tertiary care centre in India - Jaya Chawla; Neena Sharma; Devendra Arora; Manisha Arora; Lovely Shukla (Elsevier, 2018)
Objective: Osteoporosis is a skeletal disorder characterized by diminished bone strength that increases the risk of fracture at instances of trivial trauma. Asians have a lower bone mass than the west. The present study was designed to add data from India on women above the age of 40 years with respect to low bone mineral density (BMD) and its associated high risk factors. Materials and Methods: After a written informed consent, a detailed history was taken. Basal metabolic index was recorded, and biochemical and endocrine tests were done, followed by dual X ray absorptiometry scan. Results: Average age of the study population was 46.54 years and BMI 26.58. The prevalence of osteopenia in the study was 36%, and that of osteoporosis, 4%; the overall prevalence of low BMD being 40%. Proportion of women with low BMD increased with advancing age and menopausal status. On endocrine evaluation, 53.44% cases with insufficient vitamin D, 62.5% with hyperparathyroidism, 100% with hypothyroidism, 75% with hyperthyroidism suffered from low BMD. Among chronic diseases, 75% women with diabetes, 33.3% with hypertension, 25% with deranged liver function and 50% with rheumatoid arthritis were found to have low BMD. 46.75% women with sun exposure less than one hour daily had poor bone mineralization. The proportion of women with normal BMD decreased from 84.09% to 43.33% with decrease in daily physical work. On logistic regression analysis, insufficient serum vitamin D concentrations, less physical work and inadequate sun exposure were found to be significantly associated with low BMD. Conclusion: Low BMD is not a disorder confined to postmenopausal women alone. It is widely prevalent in women above 40 years of age. Screening women above 40 in the absence of any high risk factors has the potential of nipping this silent killer in the bud.